Climate-and nutrition-smart orange-fleshed sweetpotato, Ethiopia. Food biofortification for health. Project profile. - International Potato Center (International Potato Center, 2019)
In addition to providing a valuable source of energy, orange-fleshed sweetpotato is rich in vitamin A. It is an ideal staple to grow in densely populated and drought-prone countries, like Ethiopia. This project aims to improve food security and nutrition among smallholders and the urban poor through a package of interventions that improve both supply of and demand for this valuable food source.